Human Enterovirus D68 infection – the intricate dance of cells, genes, and invading bugs - Lillerovde Ørstenvik, Hanne; Tveten, Ann-Kristin; Cao, Yanran (Frontiers in Cellular and Infection Microbiology, 2025)
The respiratory tract is particularly vulnerable to infections from various pathogens, often leading to severe illnesses. Co-infections involving multiple pathogens are commonly observed in respiratory diseases, although their underlying mechanisms remain poorly understood. Lung epithelial cells play a crucial role in the body’s defense and are primary targets for many pathogens, which exploit them for attachment and entry. This study investigates the molecular mechanism underlying co-infections of human enterovirus D68 (HEV-D68) and bacteria (Group A Streptococcus and Streptococcus pneumoniae) in lung epithelial cells. Cell viability and gene expression changes were assessed over a 24-hour period. The results revealed significant cytopathic effect and distinct gene expression patterns. HEV-D68 infection alone induced stronger upregulation of mucin genes (MUC2, MUC5AC) and immune markers (TNFα and p38) compared to co-infections. In contrast, co-infections led to downregulation of sialic acid biosynthesis genes (CMAS, GNE, NANS), suggesting impaired receptor restoration and altered host-pathogen dynamics. These findings contribute to a deeper understanding of epithelial responses and highlight potential therapeutic targets.